Urban development of Bratislava: suburbanization in years 1995-2009 - Tóth, Vladimir (Journal for Geography, 2012)
This paper deals with 14 years of urban development in Bratislava, especially aimed at the suburbanization processes. The main subject of this paper is to find the spatial shape of suburbanization in that case, the intensity of suburbanization and the regularities suburbanization occurs under. Furthermore, the main goal of this paper supposes suburbanization to be dynamic and changing throughout the derived time framework. Confirmation of this has to be done together by theoretical and empirical knowledge. All above mentioned assumptions have been confirmed.